Decreased Mortality with Beta-Blocker Therapy in HFpEF Patients Associated with Atrial Fibrillation. (13th May 2020) - Yang, Yanhua; Guo, Suxia; Huang, Ziyao; Deng, Chunhua; Chen, Lihua; Zhou, Guoxiang; Jian, Zhengwei; He, Ruping; Huang, Zhichao; Yao, Yongzhao; Lu, Jiongbin; Hua, Zhiwen; et al.
Abstract : Background . There are no proven effective treatments that can reduce the mortality in heart failure with preserved ejection fraction (HFpEF), probably due to its heterogeneous nature which will weaken the effect of therapy in clinical studies. We evaluated the effect of beta-blocker treatment in HFpEF patients associated with atrial fibrillation (AF), which is a homogeneous syndrome and has seldom been discussed. Methods . This retrospective cohort study screened 955 patients diagnosed with AF and HFpEF. Patients with a range of underlying heart diseases or severe comorbidities were excluded; 191 patients were included and classified as with or without beta-blocker treatment at baseline. The primary outcome was all-cause mortality and rehospitalization due to heart failure. Kaplan-Meier curves and multivariable Cox proportional-hazards models were used to evaluate the differences in outcomes. Results . The mean follow-up was 49 months. After adjustment for multiple clinical risk factors and biomarkers for prognosis in heart failure, patients with beta-blocker treatment were associated with significantly lower all-cause mortality (hazard ratio (HR) = 0.405, 95% confidence interval (CI) = 0.233–0.701, p = 0.001 ) compared with those without beta-blocker treatment. However, the risk of rehospitalization due to heart failure was increased in the beta-blocker treatment group (HR = 1.740, 95% CI = 1.085–2.789, p = 0.022 ). There was no significant difference in all-cause rehospitalization between the two groups (HR = 1.137, 95% CI = 0.803–1.610, p = 0.470 ). Conclusions . In HFpEF patients associated with AF, beta-blocker treatment is associated with significantly lower all-cause mortality, but it increased the risk of rehospitalization due to heart failure.